If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3 = 7 Reorder the terms: 3 + 2y = 7 Solving 3 + 2y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 7 + -3 2y = 7 + -3 Combine like terms: 7 + -3 = 4 2y = 4 Divide each side by '2'. y = 2 Simplifying y = 2
| 11.2+4(2.1+q)=-0.8 | | 2ax-2by+4bx-ay=0 | | 3x+4yi=(7-5i)2 | | (2x-8)2=15 | | 4x-36rx+32=0 | | 0+10*1-60-60*10+10= | | 7+3(2n+6)-n= | | 8b-64a=8 | | 11x=286 | | 3(4x-6)+18= | | 2x-1=14-x | | 4z+3=6+2z | | 21-n+36= | | m+60=m+303 | | m+60=p+303 | | 6x-16=32 | | 5x+9=5+3x | | l=90(0+m)-3 | | 60=10p | | -7=117 | | 12-25+6=177 | | 3(x+2)-2(x-1)=7 | | y-21/3=-3 | | 85-79=27y-33y | | -n=5 | | x-6=34+34+3x | | x-6=34+34 | | -s=9 | | 2.3=x-5.9 | | x-6=34+x | | 39=z+51 | | 2d=5d-60 |